2020
DOI: 10.15869/itobiad.748770
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Migration and Economic Growth in Turkey: Toda-Yamamoto Causality Test

Abstract: Bu makale, en az iki hakem tarafından incelenmiş ve intihal içermediği teyit edilmiştir. / This article has been reviewed by at least two referees and confirmed to include no plagiarism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
(2 reference statements)
1
4
0
5
Order By: Relevance
“…Bu nedenle, bu tür serilerin analizinde Granger nedensellik testi yerine Toda-Yamamoto nedensellik testi tercih edilmektedir. Zira vektör otoregresif (VAR) modele dayanan Toda-Yamamoto (1995) testi, modeldeki değişkenlerin aynı dereceden durağan olup olmadığına bakmaksızın düzeyde model tahmini yapabilmektedir (Meçik ve Koyuncu, 2020, s. 2625-2626.…”
Section: Toda-yamamoto Nedensellik Testiunclassified
See 1 more Smart Citation
“…Bu nedenle, bu tür serilerin analizinde Granger nedensellik testi yerine Toda-Yamamoto nedensellik testi tercih edilmektedir. Zira vektör otoregresif (VAR) modele dayanan Toda-Yamamoto (1995) testi, modeldeki değişkenlerin aynı dereceden durağan olup olmadığına bakmaksızın düzeyde model tahmini yapabilmektedir (Meçik ve Koyuncu, 2020, s. 2625-2626.…”
Section: Toda-yamamoto Nedensellik Testiunclassified
“…eşitlikleri ile gösterilmektedir. Ancak Toda-Yamamoto nedensellik işleminin uygulanabilmesi için değerinin, değerini aşmaması gerekmektedir (Meçik ve Koyuncu, 2020, s. 2626Riyath, 2018, s. 7).…”
Section: Toda-yamamoto Nedensellik Testiunclassified
“…İnterestingly, they find that immigration positively affects the unemployment and economic growth both. A similar study by Meçik and Koyuncu (2020) analyse the causality between economic growth and total immigration in Turkey for annual data between 1991 and 2018. They find unidirectional causality from immigration to economic growth.…”
Section: Related Literature and Contributionmentioning
confidence: 99%
“…The study found that there is a bilateral causality between external immigration and economic growth in Turkey, according to Granger Causality test result. Recently, Meçik and Koyuncu (2020) determined the causality relationship between economic growth of Turkey and international migration flows to Turkey using Toda-Yamamoto technique for the period 1991-2018. They discovered that there is a unidirectional causality from migration to economic growth.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…There are many previous studies (Yapraklı and Sağlam, 2010;Algan et al, 2017, Özkan andÇelik, 2018) regarding the effect of ICT on growth and studies (Meçik and Koyuncu, 2020) about international migration-economic growth nexus in Turkey. As a contribution to the literature, this paper will test the role of ICT on both external immigration movements to Turkey and economic growth in Turkey.…”
mentioning
confidence: 99%